2020
DOI: 10.1007/s13524-020-00895-3
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Fertility Transition in England and Wales: The Role of Social Class and Migration

Abstract: We use individual-level census data for England and Wales for the period 1851-1911 to investigate the interplay between social class and geographical context determining patterns of childbearing during the fertility transition. We also consider the effect of spatial mobility or lifetime migration on individual fertility behavior in the early phases of demographic modernization. Prior research on the fertility transition in England and Wales has demonstrated substantial variation in fertility levels and decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
6
0
3
Order By: Relevance
“…Finally, this anal y sis was enabled by the grow ing avail abil ity of his tor i cal cen sus data and new meth ods in the anal y sis of child nam ing. Complementing other work that lev er aged his tor i cal microdata to study behav ior and fer til ity (Guinnane et al 2006;Jaadla et al 2020;Klüsener et al 2019), this study found that nam ing is a com pel ling and increas ingly ana lyz able behav ior with respect to demo graphic change. The value of using names to under stand pop u la tion pat terns is underscored by prior ana ly ses of how nam ing relates to fer til ity behav ior (Goldstein and Stecklov 2016a;Hacker 1999), immi grant assim i la tion (Abramitzky, Boustan, and Connor 2020;Abramitzky, Boustan, and Eriksson 2020;Goldstein and Stecklov 2016a), and mor tal ity (Cook et al 2016), as well as how sur names relate to social mobil ity (Clark et al 2015;Connor 2020).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Finally, this anal y sis was enabled by the grow ing avail abil ity of his tor i cal cen sus data and new meth ods in the anal y sis of child nam ing. Complementing other work that lev er aged his tor i cal microdata to study behav ior and fer til ity (Guinnane et al 2006;Jaadla et al 2020;Klüsener et al 2019), this study found that nam ing is a com pel ling and increas ingly ana lyz able behav ior with respect to demo graphic change. The value of using names to under stand pop u la tion pat terns is underscored by prior ana ly ses of how nam ing relates to fer til ity behav ior (Goldstein and Stecklov 2016a;Hacker 1999), immi grant assim i la tion (Abramitzky, Boustan, and Connor 2020;Abramitzky, Boustan, and Eriksson 2020;Goldstein and Stecklov 2016a), and mor tal ity (Cook et al 2016), as well as how sur names relate to social mobil ity (Clark et al 2015;Connor 2020).…”
Section: Discussionsupporting
confidence: 52%
“…From 1860 to 1940, the aver age num ber of live births per mar ried woman in Britain fell from six to two (Szreter 1996). Despite decades of research across many countries, vibrant inves ti ga tions into the fer til ity decline con tinue (Beach and Hanlon 2019;Hacker 2020;Hacker and Roberts 2017;Jaadla et al 2020;Klüsener et al 2019).Thiscon tin uedworkreflectsthemanyunansweredques tions of how and why fer til ity rates decline, aided by the novel insights enabled by improv ing data sources (e.g., Ruggles et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few excep tions (Dribe and Eriksson 2019;Hacker and Roberts 2017;Jennings et al 2012;Rotering and Bras 2015), research on kin and repro duc tion in Europe and North America has focused on the period prior to the demo graphic tran si tion (circa 1870-1930). This is unfor tu nate, because the longterm decline in kin prox im ity accom pa ny ing eco nomic mod ern i za tion likely played an impor tant role in the fer til ity tran si tion (Jaadla et al 2020;Nelson 2020;Newson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this analysis was enabled by the growing availability of historical census data and new methods in the analysis of child naming. Complementing other work that leverages historical microdata to study behavior and fertility (Guinnane et al, 2006;Jaadla et al, 2020;Klüsener et al, 2019), naming is a compelling and increasingly analyzable behavior with respect to demographic change. The value of using names to understand population patterns is underscored by prior analyses of how naming relates to fertility behavior (Goldstein & Stecklov, 2021;Hacker, 1999), immigrant assimilation (Abramitzky, Boustan, & Connor, 2020;Abramitzky, Boustan, & Eriksson, 2020;Stecklov & Goldstein, 2016), mortality (Cook et al, 2016) and the use of last names to study social mobility (Clark et al, 2015;Connor, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…From 1860 to 1940, the average number of live births per married woman in Britain fell from six to two (Szreter, 1996). Despite decades of research across many countries, vibrant investigation into the fertility decline continues (Beach & Hanlon, 2019;Hacker, 2020;Hacker & Roberts, 2017;Jaadla et al, 2020;Klüsener et al, 2019). This continued work reflects the many unanswered questions of how and why fertility rates decline, aided by the novel insights enabled by improving data sources (e.g.…”
Section: Introductionmentioning
confidence: 99%